Development of Cognitive Ability Test Instrument Based on Revision Bloom Taxonomy on Dynamic Electricity Materials For Students of Senior High School - Nurmaya, Eka; Rusilowati, Ani; Astuti, Budi (Universitas Negeri Semarang, 2022)
This study aims to develop a cognitive ability test instrument based on Bloom's taxonomy revision. The test instrument covers the cognitive domains C1 (remembering), C2 (understanding), C3 (applying), C4 (analyzing), C5 (evaluating), and C6 (creating). The research was carried out using research and development methods using a 4-D development model (Define, Design, Develop, Disseminate). The research data obtained is analyzed quantitatively to determine the validity, discriminatory power, reliability, and level of difficulty of the cognitive ability test instrument. Results of research based on the analysis of the validity test showed that the test instrument was declared valid by material experts and evaluation experts with an average value of 92.65. Based on the analysis of the validity of the item validity test, there are two invalid questions, namely questions number 2 and 10. Based on the results of analyzing differentiating power, the results of question number 20 are obtained, 64 for essay questions. Based on the analysis of the level of difficulty, the results showed that the test instrument was at 5% percent of the questions at the difficulty level, 20% at the sufficient level, 70% at the medium level, and 5% at the easy level. Overall, the test instrument is valid, reliable, has good discriminating power, and has varying levels of difficulty.